2019
DOI: 10.14198/jhse.2020.153.05
|View full text |Cite
|
Sign up to set email alerts
|

Programming of physical education and health-improving classes for the girls aged 12-13 years

Abstract: The research study presents the results of the pedagogical experiment that lasted during 2017-2018 academic year. Altogether 101 girls aged 12-13 years who, for reasons of health, are classified as primary and preparatory medical groups, were involved in the research. The purpose of the research was to determine the appropriate standards of physical fitness of 12-13-year old girls, which provide a stable level of physical health. To achieve this goal, an integrated approach was used using the following researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
2
9
0
1
Order By: Relevance
“…We observed an improvement in the physical condition of young women who participated in the program. Our results support and corroborate the results of previous studies on the effectiveness of combined programs for improving coordination skills (Truszczynska-Basza et al, 2015), the functional state of the cardiorespiratory system (Baker et al, 2020), physical development (Vysotskaya et al, 2020;Goncharova et al, 2020), and physical fitness (Galan et al, 2019b). The findings of our study are consistent with the data of Yarmak et al (2019) about the beneficial effects of exercise training.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed an improvement in the physical condition of young women who participated in the program. Our results support and corroborate the results of previous studies on the effectiveness of combined programs for improving coordination skills (Truszczynska-Basza et al, 2015), the functional state of the cardiorespiratory system (Baker et al, 2020), physical development (Vysotskaya et al, 2020;Goncharova et al, 2020), and physical fitness (Galan et al, 2019b). The findings of our study are consistent with the data of Yarmak et al (2019) about the beneficial effects of exercise training.…”
Section: Discussionsupporting
confidence: 93%
“…According to Ivaschenko et al (2008), the most effective is a combined approach. The effectiveness of using combined exercise programs for people of various ages has been demonstrated in the studies of Galan et al (2019b) and Zhygalova (2003). Ivaschenko et al (2008) found that the most optimal training mode is a mixed physical activity that combines mainly aerobic exercises with anaerobic ones, which are performed in the form of short repetitions.…”
Section: Discussionmentioning
confidence: 99%
“…The key indicators that determine the level of physical development include individual functional and motor capabilities of children: aerobic endurance, strength and speedstrength abilities, as well as the ratio of height-weight indicators expressed in body mass index (BMI). Their priority is due to the most significant correlation coefficients [15] with the main components of physical health.…”
Section: Methodsmentioning
confidence: 99%
“…Those mistakes on the concept of learning need to be fixed as soon as possible because physical education is strategic subjects for educating the students to be tough inside in undergoing everyday life in society. Physical education learning is prioritized to build harmony between the big influence on the students' body and also the influence on daily life (Galan et al, 2020). By carrying out the right learning, the students are able to become qualified and competitive figures, and are expected to be able to use their competence to participate actively in the family and community.…”
Section: Aspectsmentioning
confidence: 99%